Photocatalytic Synthesis of Oxetane Derivatives by Selective CH Activation. Issue 13 (20th June 2014) - Ravelli, Davide; Zoccolillo, Matteo; Mella, Mariella; Fagnoni, Maurizio
Abstract The selective C(sp3)H activation at position 2 in oxetanes has been accomplished by decatungstate photocatalysis under mild conditions. The resulting α‐oxy radicals were trapped by electron‐poor olefins resulting in the smooth preparation of 2‐substituted oxetanes. The chemoselectivity in hydrogen abstraction in substituted oxetanes containing other H donating groups, such as CH2OH, CH2OAc and CHO, has been demonstrated in intramolecular models. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>